DEGRADAÇÃO DE 2,4,6-TRICLOROFENOL E DE 2,4,6-TRIBROMOFENOL POR FOTOCATÁLISE HETEROGÊNEA - Oliveira, Jussiane S. d. S. d.; Silveira, Leandro G. d.; Santos, Eliane P. d. (Salão do Conhecimento, 2013)
Resumo